Determination of appropriate grid dimension and sampling plot size for assessment of woody species diversity in Zagros Forest, Iran - ALI ASGHAR ZOHREVANDI; HASSAN POURBABAEI; REZA AKHAVAN; AMIR ESLAM BONYAD (Biodiversitas Journal of Biological Diversity, 2016)
Zohrevandi AA, Pourbabaei H, Akhavan R, Bonyad AE. 2015. Determination of appropriate grid dimension and sampling plotsize for assessment of woody species diversity in Zagros Forest, Iran. Biodiversitas 17: 24-30. This research was conducted to determinethe most suitable grid (dimension for sampling) and sampling plot size for assessment of woody species diversity in protected Zagros forests, west of Iran. Sampling was carried out using circular sample plots with areas of 1000 m2, 1500 m2 and 2000 m for 9 grid sizes in 200 ha forest area. Importance-value curve which fitted by a Lognormal Distribution Model was plotted using Species Importance Value Index (SVI). After determining the diversity indices such as Hills (N0, N1, N2) andÂ Alataloâ€™s evenness (E5) in each plot and assigning each sampling time, E%2x T criterion was calculated in order to compare the methods. Results of hundred percent inventory and sampling in forests showed that the accuracy of sampling in 1000m2 plot size is higher than 2000m2 ones. According to the Importance-value curve, accuracy and E%2x T criterion, the 150 m x 400 m grid size and sampling plot size with an area of 1000 m2 was proposed as the most appropriate one to estimate woody species diversity in Iranian Zagros Forests.